Bio-based products. Use of stable isotope ratios of Carbon, Hydrogen, Oxygen and Nitrogen as tools for verification of the origin of bio-based feedstock and characteristics of production processes. Overview of relevant existing applications. (17th August 2021) - British Standards Institution,
No abstract available